Extreme Hydrological Events: New Concepts for Security - Vasiliev, O.F; Gelder, P.H.A.J.M.van; Plate, E.J; Bolgov, M.V (NATO Science Series: IV:, Earth and Environmental Sciences ;, 2007)
This proceedings contains the papers which were presented at the NATO Advanced Research Workshop (ARW) on Extreme Hydrological Events: New Concepts for Security, which was held in Novosibirsk, Russia, from July 11-15, 2005. The workshop fell within the NATO priority research topic on Environmental Security, Disaster Forecast and Prevention. At the present time, the necessity of considerable deepening of our understanding about the nature of extreme and catastrophic natural and man-induced events, in particular hydrologic ones, becomes very topical, as well as the development of advanced methods for their prediction, including estimating probability of their occurrence and a risk related to them. Another aspect of this hydrological problem is reducing of vulnerability of social, economic, and engineering systems to the extreme hydrologic events (EHE) and decreasing of a degree of their effect on such systems. Dealing with these problems needs further refining existing tools for prediction and forecasting of EHE. It can be done essentially through revealing mechanisms of their generation and with use of new approaches and methodologies in related branches of hydrology. This ARW is targeted to contribute to the critical analysis and assessment of current knowledge on a number of the key issues of hydrology, such as: extreme hydrological phenomena, problems of floods, low flows and droughts. In view of significant economic losses and actually wide geographical occurrence, investigation of these hydrological phenomena is of great scientific and practical importance.